"Molecular Activity Painting": Switch‐like, Light‐Controlled Perturbations inside Living Cells. Issue 21 (29th March 2017) - Chen, Xi; Venkatachalapathy, Muthukumaran; Kamps, Dominic; Weigel, Simone; Kumar, Ravi; Orlich, Michael; Garrecht, Ruben; Hirtz, Michael; Niemeyer, Christof M.; Wu, Yao‐Wen; Dehmelt, Leif
Abstract: Acute subcellular protein targeting is a powerful tool to study biological networks. However, signaling at the plasma membrane is highly dynamic, making it difficult to study in space and time. In particular, sustained local control of molecular function is challenging owing to the lateral diffusion of plasma membrane targeted molecules. Herein we present "molecular activity painting" (MAP), a novel technology which combines photoactivatable chemically induced dimerization (pCID) with immobilized artificial receptors. The immobilization of artificial receptors by surface‐immobilized antibodies blocks lateral diffusion, enabling rapid and stable "painting" of signaling molecules and their activity at the plasma membrane with micrometer precision. Using this method, we show that painting of the RhoA‐myosin activator GEF‐H1 induces patterned acto‐myosin contraction inside living cells. Abstract : Picture this : "Molecular activity painting" enables direct and stable "painting" of signaling molecules and their activity at the plasma membrane in living cells. This is achieved by photo‐uncaging of a chemical dimerizer, which is anchored at the plasma membrane by surface immobilized artificial receptors.